High-forming-quality easy-to-evaporate light alloy laser additive and manufacturing method thereof

By dispersing the micron-scale TiC ceramic reinforced phase in the light alloy matrix, the metallurgical defects caused by the evaporation of light alloys in laser additive manufacturing are solved, and the improvement of high forming quality and mechanical properties is achieved.

CN119753396APending Publication Date: 2025-04-04NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411738868.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, light alloys such as magnesium alloys and aluminum alloys are prone to evaporation rapidly during laser additive manufacturing, resulting in metallurgical defects such as splashing and pores, and reducing the forming quality.

Method used

By dispersing the micron-scale TiC ceramic reinforced phase in the light alloy matrix, the laser absorption of the powder is improved, and the momentum of metal steam is absorbed by unmelted ceramic particles during laser forming, reducing powder splash and pore formation.

Benefits of technology

It significantly reduces the metallurgical defects of light alloys, improves the forming quality and mechanical properties, and enhances the laser absorption rate of the material and the stability of the powder bed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753396A_ABST
    Figure CN119753396A_ABST
Patent Text Reader

Abstract

The invention discloses a high-forming-quality easy-to-evaporate light alloy laser additive and a manufacturing method thereof. The high-forming-quality easy-to-evaporate light alloy laser additive comprises a light alloy matrix and a micron-sized ceramic reinforced phase dispersed in the light alloy matrix. The light alloy matrix is magnesium alloy or aluminum alloy; the micron-sized ceramic reinforced phase is TiC, the TiC ceramic reinforced phase accounts for 2-6wt.% of the content of the light alloy matrix, and the micron-sized ceramic reinforced phase TiC is tightly adhered to the surface of the light alloy matrix powder through a low-energy ball milling method. Due to the low melting point, metal elements such as magnesium and aluminum in the light alloy are prone to evaporation under irradiation of high-energy laser beams, metallurgical defects such as splashing and air holes are formed, and therefore the forming quality and the mechanical property of the light alloy are reduced. By adding a proper amount of matched reinforcement phase, the momentum of easily evaporated light alloy powder such as magnesium alloy and aluminum alloy in the laser forming process is reduced, alloy powder splashing is reduced, the forming quality of the alloy is improved, the effect of improving the laser forming property and mechanical property of the light alloy is achieved, and finally the light alloy with high forming quality and high performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of easy-to-evaporate light alloy laser additive manufacturing, and specifically relates to an easy-to-evaporate light alloy laser additive manufacturing with high forming quality and a manufacturing method thereof. Background Art

[0002] Light alloys such as magnesium alloys and aluminum alloys are widely used in aerospace, automotive and medical industries due to their advantages such as high specific strength and corrosion resistance. Laser additive manufacturing technology can directly use digital models to freely manufacture complex components, with the advantages of flexible design and high material utilization. Light alloys such as magnesium alloys and aluminum alloys contain low-melting-point metal elements Mg and Al, which are easy to evaporate quickly under the action of high-energy laser beams, forming metallurgical defects such as splashes and pores, thereby reducing the forming quality of light alloys. By adding an appropriate amount of matching reinforcement phase to the light alloy, the laser absorption of the powder in the powder bed is improved. At the same time, during the laser forming process, the high-melting-point ceramic particles are partially melted, and at the high initial injection velocity of the metal vapor, the unmelted ceramic particles will be ejected into the metal vapor. Due to the relatively high density, the momentum of the metal vapor can be absorbed and reduced by the ejected ceramic particles, reducing the powder splash of the alloy powder bed and improving the stability of the powder bed, thereby reducing the formation of defects such as pores and spheroidization, and ultimately improving the laser forming quality and mechanical properties of the alloy. Summary of the invention

[0003] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for manufacturing easy-to-evaporate light alloy laser additive with high forming quality in view of the shortcomings of the prior art, so as to give full play to the positive effects of adaptation enhancement relative laser absorption and powder bed stability, and improve the forming quality of the material.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A high-forming quality, easy-to-evaporate light alloy laser additive material comprises a light alloy matrix and a micron-sized ceramic reinforcement phase dispersed in the light alloy matrix; the light alloy matrix is ​​a magnesium alloy or an aluminum alloy; the micron-sized ceramic reinforcement phase is TiC, and the TiC ceramic reinforcement phase accounts for 2-6 wt.% of the light alloy matrix; the micron-sized ceramic reinforcement phase TiC is tightly adhered to the surface of the light alloy matrix powder by a low-energy ball milling method.

[0005] As one option, the magnesium alloy is a Mg-Al alloy, wherein the Al content is 8.2-9.0 wt.%.

[0006] As another option, the aluminum alloy is an Al-Mg alloy, wherein the Mg content is 3.9-5.5 wt.%.

[0007] Preferably, the content of the micron-sized ceramic reinforcement phase TiC dispersed in the magnesium alloy matrix is ​​2-5 wt.%, the particle size distribution range is 2-5 μm, and the purity is greater than 99.5%.

[0008] Preferably, the content of the micron-sized ceramic reinforcement phase TiC dispersed in the aluminum alloy matrix is ​​3-6 wt.%, the particle size distribution range is 2-5 μm, and the purity is greater than 99.5%.

[0009] In the present invention, TiC ceramics have a low lattice mismatch rate with metal elements such as Mg and Al, and have good interface compatibility, making them ideal reinforcement materials. TiC particles have a high laser absorptivity (>90%), which can promote the full melting and spreading of high laser reflectivity light alloys during laser additive manufacturing, and the relatively high-density ceramic particles will reduce the momentum of the powder during the powder splashing process, reduce powder splashing, and thus improve the powder bed stability and the quality of light alloy laser forming.

[0010] Furthermore, the present invention also provides a method for manufacturing the above-mentioned high-forming quality easy-to-evaporate light alloy laser additive material, comprising the following steps: (1) Mixing micron-sized TiC ceramic powder and light alloy matrix powder by low-energy ball milling under inert gas protection to obtain composite powder; the light alloy matrix is ​​magnesium alloy or aluminum alloy; (2) Establish a 3D solid geometric model of the part to be formed, then slice the geometric model and plan the laser scanning path, discretize the 3D solid into a series of 2D data, save and import them into the laser powder bed fusion forming equipment; (3) The laser powder bed fusion forming equipment melts and solidifies the composite powder in step (1) layer by layer according to the data imported in step (2), and finally forms a high-quality light alloy part.

[0011] As one option, in step (1), the light alloy matrix powder is Mg-Al alloy powder, wherein the Al content is 8.2-9.0 wt.%, the powder particle size range is 23-53 μm; and the content of micron-sized ceramic reinforcement phase TiC in the light alloy matrix is ​​2-5 wt.%.

[0012] As another option, in step (1), the light alloy matrix powder is Al-Mg alloy powder, wherein the Mg content is 3.9-5.5 wt.%, the powder particle size range is 21-56 μm, and the content of micron-sized ceramic reinforcement phase TiC in the light alloy matrix is ​​3-6 wt.%.

[0013] Preferably, in step (3), when the light alloy matrix is ​​a magnesium alloy, the laser power used by the laser powder bed fusion forming equipment is 120-180 W, the laser scanning speed is 300-600 mm / s; the scanning interval is 90 μm, the powder thickness is 40 μm, and the laser powder bed fusion forming equipment adopts an XY cross scanning strategy in which adjacent layers are rotated 90°.

[0014] Preferably, in step (3), when the light alloy substrate is an aluminum alloy, the laser power used by the laser powder bed fusion forming equipment is 300-400 W, the laser scanning speed is 500-900 mm / s, the scanning interval is 60 μm, the powder thickness is 40 μm, and the laser powder bed fusion forming equipment adopts an XY cross scanning strategy in which adjacent layers are rotated 90°.

[0015] The laser powder bed fusion forming process is as follows: (a) The powder spreading device evenly spreads the powder to be processed on the forming substrate, and the laser beam scans the slicing area layer by layer according to the pre-designed scanning path, causing the powder layer to melt / solidify rapidly, thereby obtaining the first two-dimensional plane of the part to be formed; (b) The computer control system causes the forming substrate to drop by a powder layer thickness, while the piston of the powder supply cylinder rises by a certain powder layer thickness, and the powder spreading device re-lays a layer of powder to be processed. The high-energy laser beam completes the second layer of powder scanning according to the slicing information to obtain the second two-dimensional plane of the part to be formed; (c) Repeat step (b), and the powder to be processed is formed layer by layer until the part to be formed is completed.

[0016] The above laser parameters are determined after process optimization. According to the microstructure and performance characteristics of the easily evaporated light alloy, the laser process parameters can be reasonably selected to effectively adjust the enhanced morphology, size and distribution state, and successfully prepare a light alloy with good forming quality and excellent comprehensive performance. Beneficial Effects

[0017] (1) The present invention adds micron-sized TiC ceramic particles to the light alloy powder and tightly adheres to the substrate. Due to the high melting temperature, the ceramic particles are partially melted. At the high initial velocity of the metal vapor, the unmelted ceramic particles will be sprayed into the metal vapor. Considering that the density of the metal vapor is relatively high compared with magnesium alloy and aluminum alloy, the momentum of the metal vapor can be absorbed and reduced by the sprayed ceramic particles, so that the amount of alloy powder sputtering is reduced, the stability of the powder bed is improved, and the sputtering of the powder in the powder bed is reduced, thereby reducing the formation of defects such as pores, significantly reducing the source of cracks, and improving the quality of laser forming. At the same time, the ceramic reinforcement phase improves the laser absorption rate of the alloy powder, which is beneficial to the full melting and spreading of the powder, and improves the forming quality of the alloy.

[0018] (2) The present invention mixes micron-sized TiC ceramic powder with Mg-Al alloy powder and Al-Mg alloy powder by low-energy ball milling under inert gas protection to obtain a composite powder with uniform ceramic reinforcement phase distribution, good flowability, high laser absorption rate and suitable for laser additive manufacturing. The preparation is simple and cost-effective. The use of laser additive manufacturing to prepare easy-to-evaporate light alloys not only shortens the production cycle and improves product production efficiency, but also can form parts with complex geometric shapes with almost no subsequent machining processing. (3) The present invention can adjust the laser energy density by changing the laser power and the laser scanning speed. As the laser energy input to the powder bed changes, the thermodynamic and kinetic characteristics of the molten pool formed by the interaction between the laser and the powder bed also change. By reasonably selecting the laser process parameters and adjusting the laser energy input, the volatilization of low-melting-point elements and powder splashing can be reduced, and the generation of metallurgical defects can be reduced, thereby ultimately obtaining high forming quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0020] Figure 1 The splashing process of preparing 3 wt.% TiC / Mg-Al powder by laser additive manufacturing in Example 1.

[0021] Figure 2 The splashing process of Mg-Al magnesium alloy powder prepared by laser additive manufacturing in Example 1.

[0022] Figure 3 OM image of a 3 wt.% TiC / Mg-Al composite material sample prepared by laser additive manufacturing in Example 1.

[0023] Figure 4 Surface SEM photograph of 3 wt.% TiC / Mg-Al composite material prepared by laser additive manufacturing in Example 1.

[0024] Figure 5 SEM photograph of the surface of Mg-Al magnesium alloy sample prepared by laser additive manufacturing for comparative example 1.

[0025] Figure 6 Surface roughness of 4 wt.% TiC / Al-Mg composite material prepared by laser additive manufacturing in Example 2.

[0026] Figure 7 The surface roughness of Al-Mg magnesium alloy prepared by laser additive manufacturing in Example 2.

[0027] Figure 8 OM image of 5 wt.% TiC / Mg-Al composite material prepared by laser additive manufacturing in Example 3.

[0028] Fig. 9 Surface roughness of 1 wt.% TiC / Mg-Al composite material prepared by laser additive manufacturing in comparative example 2. DETAILED DESCRIPTION

[0029] The present invention can be better understood with reference to the following examples.

[0030] In the following embodiments, when the light alloy matrix used is Mg-Al alloy, the Al content is 8.2-9.0 wt.%, and the powder particle size range is 23-53 μm; when the light alloy matrix used is Al-Mg alloy, the Mg content is 3.9-5.5 wt.%, and the powder particle size range is 21-56 μm. The particle size distribution range of the TiC ceramic powder used is 2-5 μm, and the purity is not less than 99.5%. Example 1

[0031] (1) Micron-sized TiC ceramic powder and Mg-Al alloy powder were mixed uniformly by low-energy ball milling under inert gas protection to obtain composite powder, and the ceramic mass accounted for 3 wt.% of the total mass of the powder. The process used a ceramic jar, and the ball milling medium was ceramic grinding balls with diameters of 6 mm, 8 mm and 10 mm. The ball milling process parameters were set as follows: ball-to-material ratio of 5:1, high-energy ball milling speed of 200 rpm, and ball milling time of 3 h. The ball milling process was required to be carried out under argon protection to prevent the Mg-Al alloy powder from being oxidized or contaminated during the ball milling process. After ball milling, the powder still maintained good sphericity, and the TiC ceramic particles were evenly distributed on the alloy surface and the two were tightly combined.

[0032] (2) Target part modeling and slicing The 3D solid geometric model of the target part was established using Soildworks software in the computer, and then the 3D solid model was sliced ​​and scanned using Magics software. The 3D solid was discretized into a series of 2D data, which were saved and imported into the laser powder bed fusion forming equipment. The laser process parameters were set as follows: laser power of 120 W, laser scanning speed of 300 mm / s, scanning spacing of 90 μm, powder thickness of 40 μm, and adjacent layers were rotated 90° XY cross scanning strategy.

[0033] (3) Laser powder bed fusion forming process The composite powder prepared in step (1) is used for laser powder bed fusion forming. (a) The powder spreading device evenly spreads the powder to be processed on the forming substrate, and the laser beam scans the slicing area layer by layer according to the pre-designed scanning path, so that the powder layer is quickly melted / solidified, thereby obtaining the first two-dimensional plane of the part to be formed; (b) The computer control system causes the forming substrate to drop a powder layer thickness, and the piston of the powder supply cylinder rises a certain powder layer thickness, and the powder spreading device re-lays a layer of powder to be processed. The high-energy laser beam completes the second layer of powder scanning according to the slicing information to obtain the second two-dimensional plane of the part to be formed; (c) Step (b) is repeated until a solid sample is formed layer by layer.

[0034] (4) A multi-physics model was established using DEM and CFD to simulate the interaction between powder and fluid during the LPBF process. DEM was used to simulate the movement and collision of particles, while CFD was used to simulate the thermal fluid behavior of metal vapor and surrounding gas. The sputtering of powder is mainly driven by the metal vapor generated by the melt pool and the surrounding gas above the powder bed. The model can effectively capture the metal vapor jet and its interaction with powder. According to the powder particles splashed in the theoretical simulation, the amount is ~71 ( Figure 1 ). Compared with the number of splashing powders of pure Mg-Al alloy without reinforcement phase (~119), it is reduced by ~40% ( Figure 2 ), which shows that adding an appropriate amount of reinforcing phase can effectively reduce the amount of powder splashing and improve the corresponding manufacturing quality, which is obviously different from pure magnesium alloy.

[0035] After forming is completed, the parts and substrate are separated by wire cutting to obtain Mg-Al / TiC samples. The samples are ground, polished and etched according to the standard metallographic sample preparation method. Through OM observation, the Mg-Al / TiC samples prepared by laser powder bed fusion have no obvious cracks and pores ( Figure 3 ), the density reached 99.6%. The three-dimensional surface morphology of the artificial sample was detected by laser scanning confocal microscopy, and the surface roughness of the Mg-Al / TiC sample was measured to be ~10.6 μm, which was 65% lower than that of pure Mg-Al alloy (~30.6 μm). Combined with the observation of the surface structure of the sample ( Figure 4-5 ), the surface forming quality of Mg-Al / TiC sample is obviously better. The amount of powder splashing in the simulation corresponds to the surface forming quality, which further confirms the accuracy of the simulation results. Example 2

[0036] (1) Micron-sized TiC ceramic powder and Al-Mg alloy powder were mixed uniformly by low-energy ball milling under inert gas protection to obtain composite powder, in which the ceramic mass accounted for 4 wt.% of the total mass of the powder. The process used a ceramic jar, and the ball milling medium was ceramic grinding balls with diameters of 6 mm, 8 mm and 10 mm. The ball milling process parameters were set as follows: ball-to-material ratio of 4:1, high-energy ball milling speed of 200 rpm, and ball milling time of 4 h. The ball milling process was required to be carried out under argon protection to prevent the Al-Mg alloy powder from being oxidized or contaminated during the ball milling process. After ball milling, the powder still maintained good sphericity, and the ceramic particles were evenly distributed on the alloy surface and the two were tightly combined.

[0037] (2) Target part modeling and slicing The 3D solid geometric model of the target part was established using Soildworks software in the computer, and then the 3D solid model was sliced ​​and scanned using Magics software. The 3D solid was discretized into a series of 2D data, which were saved and imported into the laser powder bed fusion forming equipment. The laser process parameters were set as follows: laser power of 300 W, laser scanning speed of 700 mm / s, scanning spacing of 60 μm, powder thickness of 40 μm, and an XY cross scanning strategy with adjacent layers rotated 90°.

[0038] (3) Laser powder bed fusion forming process The composite powder prepared in step (1) is used for laser powder bed fusion forming. (a) The powder spreading device evenly spreads the powder to be processed on the forming substrate, and the laser beam scans the slicing area layer by layer according to the pre-designed scanning path, so that the powder layer is quickly melted / solidified, thereby obtaining the first two-dimensional plane of the part to be formed; (b) The computer control system causes the forming substrate to drop a powder layer thickness, and the piston of the powder supply cylinder rises a certain powder layer thickness, and the powder spreading device re-lays a layer of powder to be processed. The high-energy laser beam completes the second layer of powder scanning according to the slicing information to obtain the second two-dimensional plane of the part to be formed; (c) Step (b) is repeated until a solid sample is formed layer by layer.

[0039] (4) A multi-physics model was established using discrete element method (DEM) and computational fluid dynamics (CFD) to simulate the interaction between powder and fluid during laser powder bed fusion (LPBF). DEM was used to simulate the movement and collision of particles, while CFD was used to simulate the thermal fluid behavior of metal vapor and surrounding gas. The sputtering of powder is mainly driven by the metal vapor generated by the melt pool and the surrounding gas above the powder bed. The model can effectively capture the metal vapor jet and its interaction with the powder. According to the splashing powder particles in the theoretical simulation, the amount is ~68. Compared with the amount of splashing powder (~115) of pure Al-Mg alloy without adding reinforcement phase, it is reduced by ~41%, which shows that adding an appropriate amount of reinforcement phase can effectively reduce the amount of splashing powder, and the corresponding manufacturing quality is improved, which is obviously different from pure aluminum alloy.

[0040] After the forming is completed, the parts and the substrate are separated by wire cutting to obtain Al-Mg / TiC samples. The samples are ground, polished and corroded according to the standard metallographic sample preparation method. Through OM observation, the Al-Mg / TiC samples prepared by laser powder bed fusion have no obvious pores, the molten pool is regular, and the density is 99.5%. The three-dimensional surface morphology of the artificial sample was detected by laser scanning confocal microscopy, and the surface roughness of the Al-Mg / TiC sample was measured to be ~8.4 μm, which is 67% lower than that of pure Al-Mg alloy (~25.7 μm), and the forming quality is significantly improved ( Figure 6-7 ). The amount of powder splash in the simulation corresponds to the surface forming quality, which confirms the accuracy of the simulation results. Example 3

[0041] (1) Micron-sized TiC ceramic powder and Mg-Al alloy powder were mixed evenly by low-energy ball milling under inert gas protection to obtain composite powder, and the ceramic mass accounted for 5wt.% of the total mass of the powder. The process used a ceramic jar, and the ball milling medium was ceramic grinding balls with diameters of 6mm, 8mm and 10mm. The ball milling process parameters were set as follows: ball-to-material ratio of 5:1, high-energy ball milling speed of 250rpm, and ball milling time of 4h. The ball milling process was required to be carried out under argon protection to prevent the alloy powder from being oxidized or contaminated during the ball milling process. After ball milling, the powder still maintained good sphericity, and the TiC ceramic particles were evenly distributed on the alloy surface and the two were tightly combined.

[0042] (2) Target part modeling and slicing The 3D solid geometric model of the target part was established using Soildworks software in the computer, and then the 3D solid model was sliced ​​and scanned using Magics software. The 3D solid was discretized into a series of 2D data, which were saved and imported into the laser powder bed fusion forming equipment. The laser process parameters were set as follows: laser power of 180 W, laser scanning speed of 600 mm / s, scanning spacing of 90 μm, powder thickness of 40 μm, and adjacent layers were rotated 90° XY cross scanning strategy.

[0043] (3) Laser powder bed fusion forming process The composite powder prepared in step (1) is used for laser powder bed fusion forming. (a) The powder spreading device evenly spreads the powder to be processed on the forming substrate, and the laser beam scans the slicing area layer by layer according to the pre-designed scanning path, so that the powder layer is quickly melted / solidified, thereby obtaining the first two-dimensional plane of the part to be formed; (b) The computer control system causes the forming substrate to drop a powder layer thickness, and the piston of the powder supply cylinder rises a certain powder layer thickness, and the powder spreading device re-lays a layer of powder to be processed. The high-energy laser beam completes the second layer of powder scanning according to the slicing information to obtain the second two-dimensional plane of the part to be formed; (c) Step (b) is repeated until a solid sample is formed layer by layer.

[0044] (4) A multi-physics model was established using DEM and CFD to simulate the interaction between powder and fluid during the LPBF process. Among them, DEM is used to simulate the movement and collision of particles, while CFD is used to simulate the thermal fluid behavior of metal vapor and surrounding gas. The sputtering of powder is mainly driven by the metal vapor generated by the melt pool and the surrounding gas above the powder bed. The model can effectively capture the metal vapor jet and its interaction with the powder. According to the splashing powder particles in the theoretical simulation, the amount is ~76. Compared with the amount of splashing powder of pure Mg-Al alloy without adding reinforcement phase (~119), it is reduced by ~36%, which shows that adding an appropriate amount of reinforcement phase can effectively reduce the amount of powder splashing, and the corresponding manufacturing quality is improved, which is significantly different from pure magnesium alloy.

[0045] After forming is completed, the parts and substrate are separated by wire cutting to obtain Mg-Al / TiC samples. The samples are ground, polished and etched according to the standard metallographic sample preparation method. Through OM observation, the Mg-Al / TiC samples prepared by laser powder bed fusion have no obvious cracks and pores. The density reaches 99.3% ( Figure 8). The three-dimensional surface morphology of the artificial sample was detected by laser scanning confocal microscopy, and the surface roughness of the Mg-Al / TiC sample was measured to be ~11.7 μm, which was 61.8% lower than that of pure Mg-Al alloy (~30.6 μm), and the forming quality was significantly improved. The amount of powder splashing in the simulation corresponds to the surface forming quality, which confirms the accuracy of the simulation results. Comparative Example 1

[0046] The steps of this comparative example are the same as those of Example 1, except that in step (1), no TiC ceramic reinforcement phase is added, and only Mg-Al alloy powder is used for laser powder bed melting forming. The amount of splashing powder in the theoretical simulation of the alloy without adding TiC ceramic reinforcement phase is ~119 ( Figure 2 After laser powder bed fusion forming, due to its low laser absorption rate and low laser energy input, metallurgical defects such as pores are generated during the forming process, resulting in low forming quality of the sample and severe surface spheroidization ( Figure 5 ), the density dropped to 96.0%, and the surface roughness was ~30.6 μm. This is because the low-melting-point elements in the Mg-Al alloy have a high tendency to evaporate under high-power laser irradiation. On the one hand, the dynamic changes in the melt flow and steam flow caused by the upward flow of these vapors will interact with the ambient gas to form a complex flow field, pushing the powder particles to erupt outward to form splashes. On the other hand, part of the vapor that cannot overflow due to rapid cooling will be retained inside the sample to form metallurgical defects such as pores, reducing the forming quality of the material. Comparative Example 2

[0047] This comparative example has the same steps as Example 1, except that in step (1), the mass of the added TiC ceramic reinforcement phase accounts for 1 wt.% of the total mass of the composite powder. It is found that the amount of splashing powder in the theoretical simulation with a low TiC reinforcement phase content increases to ~104. The sample after laser powder bed fusion forming has some pores and a surface roughness of ~29.4 μm ( Fig. 9 ). This may be because, on the one hand, the 1 wt.% TiC particles are dispersed in the matrix, and the bonding force between each other and the matrix is ​​not strong enough to effectively restrict the flow of the melt, so the spatter suppression effect is limited. On the other hand, the effect of 1 wt.% TiC addition on laser energy absorption and conduction is relatively small, and the effect on the dynamic behavior of the molten pool is limited. The molten pool is still easily disturbed by metal vapor and surrounding gas, resulting in more powder splashing, so the forming quality is not significantly improved. Comparative Example 3

[0048] This comparative example has the same steps as Example 1, except that in step (1), the mass of the added TiC ceramic reinforcement phase accounts for 10 wt.% of the total mass of the composite powder. It was found that the number of splashing powders in the theoretical simulation with a high content of TiC reinforcement phase increased to ~112, and more pores were observed in the laser formed specimens. This may be due to the excessive content of TiC particles, which led to serious agglomeration during the powder mixing process. These TiC agglomerates are difficult to be fully melted by the laser, making the molten pool unstable, and generating pores and cracks. Agglomerates will also affect the uniform absorption of laser energy, leading to local overheating and increasing the risk of splashing. In addition, excessive TiC particles will significantly reduce the plastic deformation ability of the magnesium alloy matrix. During the laser melting process, the fluidity of the molten pool is limited, which makes it difficult for the melt to be fully filled, resulting in defects such as pores and cracks, thereby reducing the forming quality.

[0049] It can be seen from Examples 1-3 and Comparative Examples 1-3 that the metallurgical defects such as spatter and porosity of the easily evaporated light alloy formed by laser additive manufacturing technology with an appropriate amount of TiC ceramic reinforcement phase are significantly reduced, and the forming quality is significantly improved. This is mainly because the addition of the TiC reinforcement phase improves the laser absorptivity on the one hand, which can promote the full melting and spreading of the high laser reflectivity light alloy during the laser additive manufacturing process, thereby improving the forming quality of the alloy. On the other hand, the unmelted ceramic particles will be ejected into the metal vapor during the laser forming process. Due to the relatively high density, the momentum of the metal vapor can be absorbed and reduced by the ejected ceramic particles, reducing the powder splash of the alloy powder bed and improving the stability of the powder bed, thereby reducing the formation of defects such as porosity and spheroidization, and ultimately improving the laser forming quality of the alloy.

[0050] The present invention provides a concept and method for high-forming quality easy-to-evaporate light alloy laser additive and its manufacturing method. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A high-forming quality, easily evaporated light alloy laser additive, characterized in that: It includes a light alloy matrix, and a micron-sized ceramic reinforcement phase dispersed in the light alloy matrix; the light alloy matrix is ​​a magnesium alloy or an aluminum alloy; the micron-sized ceramic reinforcement phase is TiC, and the TiC ceramic reinforcement phase accounts for 2-6 wt.% of the light alloy matrix; the micron-sized ceramic reinforcement phase TiC is tightly adhered to the surface of the light alloy matrix powder by low-energy ball milling.

2. The high-forming quality easy-to-evaporate light alloy laser additive according to claim 1 is characterized in that: The magnesium alloy is a Mg-Al alloy, wherein the Al content is 8.2-9.0 wt.%.

3. The high-forming quality easy-to-evaporate light alloy laser additive according to claim 1 is characterized in that: The aluminum alloy is an Al-Mg alloy, wherein the Mg content is 3.9-5.5 wt.%.

4. The high-forming quality easy-to-evaporate light alloy laser additive according to claim 2 is characterized in that: The content of micron-scale ceramic reinforcement phase TiC dispersed in the magnesium alloy matrix is ​​2-5 wt.%, the particle size distribution range is 2-5 μm, and the purity is greater than 99.5%.

5. The high-forming quality easy-to-evaporate light alloy laser additive according to claim 3 is characterized in that: The content of micron-scale ceramic reinforcement phase TiC dispersed in the aluminum alloy matrix is ​​3-6 wt.%, the particle size distribution range is 2-5 μm, and the purity is greater than 99.5%.

6. The method for manufacturing a high-forming quality easily evaporated light alloy laser additive material according to claim 1, characterized in that: The steps include: (1) Mixing micron-sized TiC ceramic powder and light alloy matrix powder by low-energy ball milling under inert gas protection to obtain composite powder; the light alloy matrix is ​​magnesium alloy or aluminum alloy; (2) Establish a 3D solid geometric model of the part to be formed, then slice the geometric model and plan the laser scanning path, discretize the 3D solid into a series of 2D data, save and import them into the laser powder bed fusion forming equipment; (3) The laser powder bed fusion forming equipment melts and solidifies the composite powder in step (1) layer by layer according to the data imported in step (2), and finally forms a high-quality light alloy part.

7. The method for manufacturing a laser additively produced easily evaporated light alloy with high forming quality according to claim 6, characterized in that: In step (1), the light alloy matrix powder is Mg-Al alloy powder, wherein the Al content is 8.2-9.0 wt.%, the powder particle size range is 23-53 μm; the content of micron-sized ceramic reinforcement phase TiC in the light alloy matrix is ​​2-5 wt.%.

8. The method for manufacturing a laser additively produced easily evaporated light alloy with high forming quality according to claim 6, characterized in that: In step (1), the light alloy matrix powder is Al-Mg alloy powder, wherein the Mg content is 3.9-5.5 wt.%, the powder particle size range is 21-56 μm, and the content of micron-sized ceramic reinforcement phase TiC in the light alloy matrix is ​​3-6 wt.%.

9. The method for manufacturing a laser additively produced easily evaporated light alloy with high forming quality according to claim 6, characterized in that: In step (3), when the light alloy matrix is ​​a magnesium alloy, the laser power used by the laser powder bed fusion forming equipment is 120-180 W, the laser scanning speed is 300-600 mm / s; the scanning interval is 90 μm, the powder thickness is 40 μm, and the laser powder bed fusion forming equipment adopts an XY cross scanning strategy in which adjacent layers are rotated 90°.

10. The method for manufacturing a laser additively produced easily evaporated light alloy with high forming quality according to claim 6, characterized in that: In step (3), when the light alloy substrate is an aluminum alloy, the laser power used by the laser powder bed fusion forming equipment is 300-400 W, the laser scanning speed is 500-900 mm / s, the scanning interval is 60 μm, the powder thickness is 40 μm, and the laser powder bed fusion forming equipment adopts an XY cross scanning strategy in which adjacent layers are rotated 90°.

Citation Information

Cited By

  • High-forming-quality volatile light alloy laser additive and manufacturing method therefor

    WO2026113239A1